Kepemimpinan Abu Bakar Al-Shiddiq (Simbol Pemersatu Umat Islam) - misrayanti; aeni, nuraeni; Syakur, Nur Ahsan (Rihlah : Jurnal Sejarah dan Kebudayaan, 2023)
Abu Bakr was born in Mecca in the year 573, approximately two years and six months after the Year of the Elephant. His full name is Abdullah, the son of Uthman, who was the son of Amir, and so on, with his lineage tracing back to Ghalib al-Qurashi At-Taimi through various ancestors. The lineage of Abu Bakr al-Siddiq intersected with the lineage of the Prophet Muhammad (peace be upon him) at their sixth-generation ancestor, Murrah bin Ka'ab. During his time as a caliph, Abu Bakr was determined to continue the military expedition led by Usamah. Usamah's forces returned to Medina with victory and war spoils (ghanimah). Additionally, another of Abu Bakr As-Siddiq's policies involved fighting false prophets and individuals who refused to pay zakat (obligatory almsgiving). Abu Bakr's leadership model was both charismatic and democratic. He was known for making firm decisions, such as taking measures to combat apostasy, resistance to paying zakat, and false prophets. When Abu Bakr As-Siddiq addressed the public, he encouraged open dialogue, allowing the voice of the community to be heard without constraints imposed by a leader's authority. This demonstrated a commitment to democratic values. Abu Bakar lahir di Mekah pada tahun 573 M atau lebih kurang dua tahun enam bulan setelah tahun Gajah. Namanya adalah Abdullah bin Utsman bin Amir bin Amr bin Ka’ab bin Sa’ad bin Taim bin Murrah bin Ka’ab bin Lu’ai bin Ghalib al-Qurasyi At-Taimi. Nasab Abu Bakar al-Shiddiq bertemu dengan nasab Nabi Muhammad Saw pada kakek keenam yaitu Murrah bin Ka’ab. Ketika menjadi khalifah Abu Bakar bertekad kuat untuk melanjutkan ekspedisi militer pimpinan Usamah. Pasukan Usamah kembali ke Madinah dengan membawa kemenangan dan harta ghanimah (harta rampasan perang). Selain itu, kebijakan lain Abu Bakar As-Shiddiq memerangi nabi palsu dan orang-orang yang tidak mau membayar zakat. Model kepemimpinan Abu Bakar karismatik dan demokratis, selain itu tegas dalam mengambil keputusan sebagaimana saat mengambil kebijakan memberantas kaum murtad, pembangkang zakat dan nabi-nabi palsu. Abu Bakar as-Shiddiq saat ia menyampaikan pidatonya di hadapan publik, dimana suara umat tidak dibatasi oleh otoritas seorang pemimpin, melainkan ia meminta masukan dan pendapat dari umat hal tersebut menunjukkan adanya penerapan nilai demokratis.